Juridical Analysis of Criminal Acts of Theft Committed by Children - Afrio Dimas Kharismajaya; Bastianto Nugroho; Sri Anggraini Kusuma Dewi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
This research aims to juridically analyze criminal acts of theft committed by children in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The crime of theft by children is an important issue that requires a special legal approach, considering the behavioral characteristics of minors. In this analysis, a normative juridical approach is used to assess the application of the law in handling cases of theft committed by children, as well as to evaluate the effectiveness and fairness of the juvenile justice system. This study includes an assessment of relevant legal provisions, implementation of child protection principles in the justice system, as well as comparisons with international standards regarding the handling of juvenile criminals. The research results show that although Law Number 11 of 2012 provides an adequate legal framework for handling cases of theft by children, there are challenges in its implementation that require further attention, including in terms of rehabilitation and social reintegration of children's behavior, that the law In general, it is in accordance with the principles of justice for children, but there needs to be improvements in several aspects to increase the effectiveness of protection and rehabilitation. It is hoped that this research will contribute to balancing the juvenile criminal justice system in Indonesia.